Hand dermatoglyphic of males suffering from schizophrenia - Budnik, Alicja; Stefaniak, Barbara (Anthropological Review, 1980)
During 1976 year fingerprints of 254 and prints of palms at 199 male subjects suffering from schizophrenia were collected in hospitals at Poznań and Gorzów Wielkopolski. All subjects were ethnically 'Polish, their age ranged from 18 to 74 years. Most of the subjects were diagnosed as having either a simple form of the disease {schizophrenia simplex) or a paranoid one (schizophrenia paranoidas). A small group of examined persons suffered from other forms of the disease (catatonia and hebephrenia). Duc to a small size of this sample it has not been studied separately, however, data on these patients were included into a joint analysis of all subjects. . Dermatoglyphes on finger were classified after Lestrange's method in its form modified by Bocheńska [Rogucka 1968]. Palmar dermatoglyphes were classified by Cummins’ method {Gladkova 1966, Łasiński 1952, Rogucka 1973]. The results obtained during the present study may be summarized as follow: 1. No significant differences were found between Total Ridge Count of schizophrenic individuals and healthy people. 2. Statistically significant differences between the sample studied and comparative material pertaining to a healthy Polish people are present in:—frequency of ridge patterns and frequency of directions of patterns on fingers—asymmetry of directions of patterns on fingers—frequency of main lines terminations on palms—pattern intensity and asymmetry on hypothenar—frequency of proper figures presence in IIT and IV interdigital area—general pattern intensity in subdigital areas (GPT)—values of pattern complexity index3. Differences between persons suffering from schizophrenia simplex and schizophrenia paranoides were found with respect to:—frequency of patterns on fingers and hypothenar—frequency of proper patterns -directions on fingersDifferences found between dermatoglyphes of individuals suffering from schizophrenia and healthy persons contributes to corroboration of a hypothesis on genetic (probably polygenic) background of schizophrenia. Simultaneously some dermaltoglyphic differences between subjects suffering from schizophrenia simplex and schizophrenia paranoides suggest that distinct forms of the disease can have divergent genetic determination.